Aroylketene dithioacetal chemistry: facile synthesis of 4-aroyl-3-methylsulfanyl-2-tosylpyrroles from aroylketene dithioacetals and TosMIC - Prakash Rao, H. Surya; Sivakumar, S. (Beilstein Journal of Organic Chemistry, 2007)
The cycloaddition of the von Leusen's reagent (p-tolylsulfonyl)methyl isocyanide (TosMIC) to α-aroylketene dithioacetals (AKDTAs) in the presence of sodium hydride in THF at rt resulted in a facile synthesis of the 4-aroyl-3-methylsulfanyl-2-tosylpyrroles 3 in good yield along with a minor amount of 4-[(4-methylphenyl)sulfonyl]-1-[(methylsulfanyl)methyl]-1H-imidazole 4. This study lead to the synthesis of 2,3,4-trisubstiuted pyrroles having 1-naphthoyl/2-naphthoyl/ferrocenoyl/pyrenoyl scaffolds on C-4 of the pyrrole ring. In this transformation, the AKDTAs behave as a 3-(methylsulfanyl)-1-aryl-2-propyn-1-one (ArCOC≡CSMe) equivalent. Competition experiments clearly showed that the cycloaddition of TosMIC to "push-pull" alkenes like AKDTAs is slower compared to general α,β-unsaturated carbonyl compounds.